Pengaruh Pemberian Ultrasound, Dan Nerve And Tendon Gliding Exercise Terhadap Penurunan Nyeri Penderita Carpal Tunnel Syndrom Di Klinik Fisioterapi H.Ds Hariyanto Dan Rekan Pekanbaru - Kurniati Kandariah; Maryaningsih Maryaningsih; Lagut Sutandra (LPPM STIKES Siti Hajar dan Insight Power, 2022)
Background: Hands are one of the limbs that are most often used in various daily activities. Excessive hand and wrist activity if it lasts a long time and is repeated can cause problems and cause problems. In the condition of carpal tunnel syndrome, physiotherapy interventions can be given in the form of ultrasound and nerve and tendon gliding exercises which aim to improve blood flow, reduce pressure on the median nerve , helps the tendons shift to their original position so as to reduce pain. Purpose: This study aims to determine the effect of ultrasound and nerve and tendon gliding exercise on reducing carpal tunnel syndrome pain. Research Method: this study used a quasi-experimental and one group pre and post test design. The sample of this study were 17 people who met the inclusion and exclusion criteria. Measuring pain scores was carried out using a visual analog scale and the results of the study were analyzed using the Friedman test. Results: The results of measurements of carpal tunnel syndrome pain showed a decrease in the pain felt by respondents, where the value of pain before being given therapy was 88.2% of respondents felt severe pain and 11.8% of respondents felt moderate pain, in the third therapy it was obtained 29.4% Respondents felt severe pain and 70.6% of respondents felt moderate pain, while in the sixth treatment 100% of respondents felt moderate pain, and in the ninth treatment 64.7% of respondents felt moderate pain and 35.3% of respondents felt mild pain. Conclusion: from this study there was an effect of ultrasound and nerve and tendon gliding exercise on reducing carpal tunnel syndrome pain..Keywords: Pain reduction, Physiotherapy exercises